Sudan's painful road to peace : a full story of the founding and development of SPLM/SPLA - Madut-Arop, Arop (BookSurge, 2006)
A record of the founding and development of the Sudan People's Liberation Movement and the Sudan People's Liberation Army and its subsequent military campaigns (1983-2005). "The author believes that the true story of the founding and development of the Sudan People Liberation Movement (SPLM) and the Sudan People Liberation Army (SPLA) and its subsequent military campaign has not been previously documented in such detail. It starts with a brief summary of the Anya Nya war (1955-1972) going through the Ten Year Truce ushered in by the Addis Ababa Peace Accord of 1972 and covers the politics which led to the founding of the SPLA in 1983. The political and military campaign of the SPLA/SPLM from 1983 up until the Comprehensive Peace Agreement in 2005 is examined in detail"--cover.